The Effectiveness of Cebra (Lecture, Brainstorming) and Cebook (Lecture, Booklet) Method to Increasing the Knowledge and Attitude Towards Genitalia Hygiene in Female Adolescent Aged 15-18 Years Old - Elmiyatin, Eva; Kusumaningrum, Tiyas; DwiKurnia, Iqlima (International Journal of Psychosocial Rehabilitation, 2020)
This study analyzed the effectiveness of health education methods about genital hygiene in female adolescents. This research used a quasi-experiment pre-post-test control group design. A total of 60 girls aged 15–18 years were chosen using the total-sampling technique. Respodents were divided into 2 groups that were given different interventions. Data analysis used Wilcoxon signed rank test and Mann-Whitney U-test with ∝= 0.05. The results showed a significant increase in the knowledge and attitudes of both groups after the Cebra and Cebook interventions (p = 0.000). There was no difference in knowledge (p = 0.054) or attitude (p = 0.067) between the two groups.